The Effect of Economic Crises on Nutritional Status : Evidence from Russia - Steven Stillman; Duncan Thomas (Institute for the Study of Labor (IZA), 2004)
This paper uses data from the Russian Longitudinal Monitoring Survey (RLMS) to examine the relationship between nutritional status and both longer-run household resources and short-run fluctuations in household resources. We evaluate six measures of nutrition – gross energy intake, two dimensions of diet quality, body mass index (BMI), which is a measure of net energy intake for adults, and for children, weight for height and stature. Our finding indicate a clear positive effect of longer-run resources on energy intake, diet composition, adult BMI, and child stature. Between 1996 and 2000, Russian households experienced a dramatic decline in income and expenditure and then an equally dramatic rise. We exploit the panel nature of RLMS to identify the causal effect of changes in household resources on nutritional status. In contrast to the large decline in expenditure in 1998, nutritional status appears to be very resilient to variation in household resources and this is reflected in gross energy intake, adult BMI, and child stature, which all change very little as expenditure deviates from its long-run average. Diet composition, however, does change in response to transitory variation in household resources. It appears that individuals and households are able to weather large economic crises at least in terms of maintaining body mass and energy intake.
Keywords: D12; P36; O12; I12; 330; nutrition; caloric intake; BMI; consumption smoothing; economic shocks; Russia; economic crises; Ernährung; Haushaltseinkommen; Verbraucherausgaben; Unterernährung; Wirtschaftskrise; Russland